Prevalence of cervical enamel projections and enamel pearls on furcation area of Iraqi molar teeth (Mustansiria Dental Journal, 2024)
Cervical enamel projections and enamel pearls in relation to molar furcationsmay act as predisposing factors in periodontal attachment loss. The objectives of thisstudy were to investigate the prevalence of cervical enamel projections and enamelpearls on furcation areas of molar teeth of Iraqi population. The material consisted of(465)extracted upper and lower molars. They were (200) upper molars and (200) )lower molars extracted because of` caries and pulp lesions(groupl), while the othermolars extracted because they were periodontally diseased(group2). The cervical )64(enamel projections were classified into three grades(described according to peter et al 2000)For group l the results showed that (5l%) of upper molars and (66%) of lowermolars had cervical enamel projections. Enamel pearls were identified on (1.5%) ofupper molars and (2.5%) of lower molars. Maxillary molars had (59.8%) grade Icervicaljnamel pro`ections and 28.4%) grade ll and (ll.7%) rade III. Whilemandibular molars showed (66.6%) teeth with grade I, (24.2%) teeth with grade IIand (9%) teeth with grade III .For grou 2 cervical enamel rojcctions were identifiedon (70.7%) ofthe collected molarsThe results of the present study give an indication that cervical enamelprojections are frequent enough to be of clinical importance